2019
DOI: 10.1177/1747021819888982
|View full text |Cite
|
Sign up to set email alerts
|

Song and infant-directed speech facilitate word learning

Abstract: Two separate lines of research have examined the influence of song and infant-directed speech (IDS—a speech register that includes some melodic features) on language learning, suggesting that the use of musical attributes in speech input can enhance language learning. However, the benefits of these two types of stimuli have never been directly compared. In this investigation, we compared the effects of song and IDS for immediate word learning and long-term memory of the learned words. This study examines wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 104 publications
1
50
0
Order By: Relevance
“…If people worldwide reliably alter their speech and song when interacting with infants, as the above findings suggest, this may enable listeners to make reliable inferences concerning the intended targets of speech and song, consistent with functional accounts of infant-directed vocalization 33,[36][37][38][39][40][41][42][43]46 . We tested this hypothesis in a simple listening experiment.…”
Section: Naïve Listeners Are Sensitive To the Acoustic Forms Of Infan...mentioning
confidence: 55%
See 1 more Smart Citation
“…If people worldwide reliably alter their speech and song when interacting with infants, as the above findings suggest, this may enable listeners to make reliable inferences concerning the intended targets of speech and song, consistent with functional accounts of infant-directed vocalization 33,[36][37][38][39][40][41][42][43]46 . We tested this hypothesis in a simple listening experiment.…”
Section: Naïve Listeners Are Sensitive To the Acoustic Forms Of Infan...mentioning
confidence: 55%
“…What enables such a diverse group of people to arrive at such similar conclusions about unfamiliar, foreign vocalizations, in languages that they do not understand? One possibility is that there exists a universal set of acoustic features driving listeners' inferences concerning the intended targets of speech and song, which are reliably instantiated within and across societies, as suggested by functional accounts of infant-directed vocalization 33,[36][37][38][39][40][41][42][43]46 .…”
Section: Acoustic Correlates Of Infant-directedness Across Culturesmentioning
confidence: 99%
“…Overall, research has produced robust evidence of a powerful relationship between characteristics of language input in terms of qualitative and quantitative individual differences, and language development outcomes in toddlers and young children (D'Odorico & Jacob, 2006;Fernald et al, 2013;Fernald & Mazzie, 1991;Romeo et al, 2018;Suttora et al, 2017;. In this framework, besides being 'as good as speech', it is possible that ID-song might even present specific contributions to language development in its own right (see also Ma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual illusions provide psychologists with other ways to examine the limits of perceptual and cognitive systems, potentially increasing our fundamental understanding of these systems [3,4,49,50]. Recent work has demonstrated that song and infant-directed speech facilitates the process of word learning in adults [51]. Because both (a register of) speech and song influence the language-related process of word-learning, further examination of auditory illusions like the Speech-to-Song Illusion might provide insight in to a wide range of other language-related processes.…”
Section: Plos Onementioning
confidence: 99%